Cerium-zirconium loaded cobalt titanate solid solution nanosphere water treatment catalyst and preparation method thereof

By using cerium-zirconium-supported cobalt titanate solid solution nanosphere catalyst, the problem of effective degradation of p-nitrophenol in existing catalytic materials only under acidic conditions is solved, and efficient degradation and good results are achieved under neutral or slightly alkaline conditions. Reusable performance.

CN119488912APending Publication Date: 2025-02-21WATER RESOURCES RES INST OF SHANDONG PROVINCE +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411618332.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the existing catalytic treatment methods, most catalytic materials can degrade more than 90% of p-nitrophenol only under acidic conditions.

Method used

Using cerium-zirconium-supported cobalt titanate solid solution nanospheres as catalysts, nanospherical iron tetroxide as the inner core, cerium-zirconium solid solution as the electron transport intermediate layer, cobalt titanate as the outer layer of active components and D-(-)-quinine As a combination of morphological control agents, an acid forms a catalyst with excellent redox properties.

Benefits of technology

This catalyst can also efficiently degrade p-nitrophenol under neutral or slightly alkaline conditions, and has good reuse performance and high mechanical strength, reducing the operating cost of water pollution control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488912A_ABST
    Figure CN119488912A_ABST
Patent Text Reader

Abstract

The invention provides a cerium-zirconium loaded cobalt titanate solid solution nanosphere water treatment catalyst and a preparation method thereof, and relates to the field of water treatment. The cerium-zirconium loaded cobalt titanate solid solution nanosphere water treatment catalyst comprises nano spherical ferroferric oxide, a cerium-zirconium solid solution, cobalt titanate and D-(-)-quinic acid, the nano spherical ferroferric oxide serves as an inner core, the cerium-zirconium solid solution serves as an electron transport middle layer, the cobalt titanate serves as an active component outer layer, and the D-(-)-quinic acid serves as a morphology control agent. On the basis of the mass of the ferroferric oxide inner core, the mass percentage content of the electron transmission middle layer is 60%-80%, and the mass percentage content of the active component outer layer is 20%-40%; wherein the molar ratio of cerium oxide to zirconium oxide in the cerium-zirconium solid solution is 1: (0.33-3). The catalyst provided by the invention is environment-friendly, not only can efficiently catalyze and reduce p-nitrophenol, but also can be repeatedly used, is simple to regenerate, and has higher economic value and wide market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment, in particular to a cerium-zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst and a preparation method thereof. Background Art

[0002] With the acceleration of industrialization, water pollution is becoming increasingly serious. Among them, p-nitrophenol, as an important organic pollutant, is widely used in the production of dyes, pesticides and drugs. However, p-nitrophenol is toxic, such as aquatic fish and aquatic invertebrates. It has obvious toxic effects and may lead to a decline in biodiversity. In addition, contact and ingestion of p-nitrophenol may cause human poisoning, and long-term contact may also lead to more serious health problems.

[0003] Traditional water treatment methods such as chemical precipitation, oxidation-reduction and biodegradation have certain limitations in removing p-nitrophenol. The chemical precipitation method has a poor removal effect on p-nitrophenol. Although the oxidation-reduction method can effectively remove some organic pollutants, it often requires a strong oxidant when treating p-nitrophenol, and the reaction conditions are harsh. The biodegradation method has limited degradation capacity for p-nitrophenol and is affected by environmental factors such as water quality and temperature. In the field of water treatment, the catalytic reduction method is a method that can completely solve water pollution and even turn waste into treasure. Sodium borohydride is used to reduce p-nitrophenol to chemical products, and the catalytic material can be recycled and reused, and will not remain in the wastewater to cause secondary pollution to the environment. However, in the existing catalytic treatment methods, most of the catalytic materials can only degrade more than 90% of p-nitrophenol under acidic conditions. Therefore, the technicians in this field provide a cerium zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst and a preparation method to solve the problems raised in the above background technology. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the shortcomings of the prior art, the present invention provides a cerium-zirconium-loaded cobalt titanate solid solution nanosphere water treatment catalyst and a preparation method, which solves the problem in the existing catalytic treatment methods that most catalytic materials can only degrade more than 90% of p-nitrophenol under acidic conditions.

[0006] (II) Technical solution

[0007] To achieve the above purpose, the present invention is implemented by the following technical scheme: a cerium zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst, comprising: nano-spherical ferroferric oxide, a cerium zirconium solid solution, cobalt titanate and D-(-)-quinic acid, wherein the nano-spherical ferroferric oxide is an inner core, the cerium zirconium solid solution is an electron transport middle layer, the cobalt titanate is an active component outer layer, and the D-(-)-quinic acid is a morphology control agent. Based on the mass of the ferroferric oxide inner core, the mass percentage of the electron transport middle layer is 60% to 80%, and the mass percentage of the active component outer layer is 20% to 40%; wherein the molar ratio of cerium oxide to zirconium oxide in the cerium zirconium solid solution is 1:0.33 to 3.

[0008] The preparation method of cerium zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst comprises the following steps:

[0009] S1. Preparation of ferroferric oxide coated with cerium zirconium solid solution, weighing nano ferroferric oxide powder, cerium salt, zirconium salt, D-(-)-quinic acid and deionized water, and then placing it in a hydrothermal reactor for hydrothermal reaction. After the reaction is completed, it is filtered and dried, and then calcined at high temperature to obtain cerium zirconium solid solution coated ferroferric oxide powder;

[0010] S2. Preparation of cobalt titanate solid solution: weigh acetic acid, deionized water and anhydrous ethanol, put them in an open beaker and stir evenly, then add titanium salt, cobalt salt and the cerium-zirconium solid solution prepared in step S1 to wrap the ferroferric oxide powder and stir evenly to form a mixed slurry, then put the mixed slurry in a water bath and stir continuously, after the titanium salt in the mixed slurry is completely hydrolyzed, add D-(-)-quinic acid and put it in a hydrothermal reactor for hydrothermal reaction, filter and dry after the reaction, and then calcine at high temperature to obtain the cobalt titanate solid solution catalyst.

[0011] Preferably, the microscopic particle size of the nano-iron tetroxide powder in step S1 is 300-400 mm, the cerium salt is cerium chloride or cerium nitrate hexahydrate, and the zirconium salt is zirconium nitrate or zirconium oxychloride octahydrate.

[0012] Preferably, in step S1, the mass ratio of nano-iron tetroxide powder, D-(-)-quinic acid and deionized water is 1:0.02-0.05:20-40.

[0013] Preferably, in step S1, the temperature of the hydrothermal reaction is 140 to 160 degrees Celsius, the time of the hydrothermal reaction is 4 to 8 hours, the temperature of the drying is 80 to 100 degrees Celsius, the time of the drying is 6 to 12 hours, the temperature of the high-temperature calcination is 500 to 600 degrees Celsius, and the time of the high-temperature calcination is 2 to 4 hours.

[0014] Preferably, the titanium salt in step S2 is tetrabutyl titanate or tetraethyl titanate, and the cobalt salt is cobalt nitrate or cobalt chloride.

[0015] Preferably, in step S2, the mass ratio of titanium salt, acetic acid, deionized water, anhydrous ethanol and D-(-)-quinic acid is 1:5-10:2-5:40-60:0.01-0.03.

[0016] Preferably, in step S2, the temperature of the water bath is 60 to 80 degrees Celsius, the stirring rate is 50-100 r / min, and the time for hydrolysis of titanic acid is 12 to 24 hours.

[0017] Preferably, in the step S2, the temperature of the hydrothermal reaction is 120 to 140 degrees Celsius, the time of the hydrothermal reaction is 6 to 12 hours, the temperature of the drying is 80 to 100 degrees Celsius, the time of the drying is 6 to 12 hours, the temperature of the high-temperature calcination is 500 to 600 degrees Celsius, and the time of the high-temperature calcination is 2 to 4 hours.

[0018] Use of the cerium-zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst according to claim 1 in catalytic reduction of organic pollutants in water, wherein the organic pollutant is p-nitrophenol.

[0019] (III) Beneficial effects

[0020] The invention provides a cerium-zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst and a preparation method thereof.

[0021] It has the following beneficial effects:

[0022] 1. In the present invention, the catalyst uses ferroferric oxide nanospheres as the core, which can ensure the recovery and reuse of the catalytic material during use. The cerium-zirconium solid solution with excellent redox performance, oxygen storage and release performance and electron transport performance is used as the electron transport intermediate layer, which can ensure the excellent redox performance of the catalytic material and enhance the catalytic effect.

[0023] 2. In the present invention, cobalt titanate has both surface acidity and excellent catalytic reduction performance, which can ensure catalytic performance. D-(-)-quinic acid can ensure that the cerium-zirconium solid solution and cobalt titanate grow uniformly on the surface of the ferroferric oxide nanospheres, maintain their nanosphere morphology, thereby promoting the increase of specific surface area, and ultimately ensuring the adsorption and activation of p-nitrophenol.

[0024] 3. In the present invention, the catalyst component is environmentally friendly, has a simple preparation process, is cost-effective, and has high mechanical strength, which can effectively reduce the operating cost of water pollution control and has strong application and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic diagram of the FE-SEM of the catalyst prepared in Example 2 of the present invention;

[0026] Figure 2This is a schematic diagram of the FE-SEM of the catalyst prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Embodiment 1:

[0029] like Figure 1-2 As shown, an embodiment of the present invention provides a cerium-zirconium-loaded cobalt titanate solid solution nanosphere water treatment catalyst, comprising: nano-spherical ferroferric oxide, a cerium-zirconium solid solution, cobalt titanate and D-(-)-quinic acid, wherein the nano-spherical ferroferric oxide is an inner core, the cerium-zirconium solid solution is an electron transport middle layer, the cobalt titanate is an active component outer layer, and the D-(-)-quinic acid is a morphology control agent. Based on the mass of the ferroferric oxide inner core, the mass percentage of the electron transport middle layer is 60% to 80%, and the mass percentage of the active component outer layer is 20% to 40%; wherein the molar ratio of cerium oxide to zirconium oxide in the cerium-zirconium solid solution is 1:0.33 to 3.

[0030] The preparation method of cerium zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst comprises the following steps:

[0031] S1. Preparation of ferroferric oxide coated with cerium zirconium solid solution, weighing nano ferroferric oxide powder, cerium salt, zirconium salt, D-(-)-quinic acid and deionized water, mixing evenly, and then placing in a hydrothermal reactor for hydrothermal reaction, filtering and drying after the reaction, and then calcining at high temperature to obtain cerium zirconium solid solution coated ferroferric oxide powder;

[0032] S2. Preparation of cobalt titanate solid solution: weigh acetic acid, deionized water and anhydrous ethanol, put them in an open beaker and stir evenly, then add titanium salt, cobalt salt and the cerium-zirconium solid solution prepared in step S1 to wrap the ferroferric oxide powder and stir evenly to form a mixed slurry, then put the mixed slurry in a water bath and stir continuously, after the titanium salt in the mixed slurry is completely hydrolyzed, add D-(-)-quinic acid and put it in a hydrothermal reactor for hydrothermal reaction, filter and dry after the reaction, and then calcine at high temperature to obtain the cobalt titanate solid solution catalyst.

[0033] The microscopic particle size of the nano-iron oxide powder in step S1 is 300-400 mm, the cerium salt is cerium chloride or cerium nitrate hexahydrate, and the zirconium salt is zirconium nitrate or zirconium oxychloride octahydrate.

[0034] In step S1, the mass ratio of nano-iron tetroxide powder, D-(-)-quinic acid and deionized water is 1:0.02-0.05:20-40.

[0035] In step S1, the temperature of the hydrothermal reaction is 140 to 160 degrees Celsius, the time of the hydrothermal reaction is 4 to 8 hours, the temperature of the drying is 80 to 100 degrees Celsius, the time of the drying is 6 to 12 hours, the temperature of the high-temperature calcination is 500 to 600 degrees Celsius, and the time of the high-temperature calcination is 2 to 4 hours.

[0036] The titanium salt in step S2 is tetrabutyl titanate or tetraethyl titanate, and the cobalt salt is cobalt nitrate or cobalt chloride.

[0037] In step S2, the mass ratio of titanium salt, acetic acid, deionized water, anhydrous ethanol and D-(-)-quinic acid is 1:5-10:2-5:40-60:0.01-0.03.

[0038] In step S2, the temperature of the water bath is 60 to 80 degrees Celsius, the stirring rate is 50-100 r / min, and the time for hydrolysis of titanic acid is 12 to 24 hours.

[0039] In step S2, the temperature of the hydrothermal reaction is 120 to 140 degrees Celsius, the time of the hydrothermal reaction is 6 to 12 hours, the temperature of the drying is 80 to 100 degrees Celsius, the time of the drying is 6 to 12 hours, the temperature of the high-temperature calcination is 500 to 600 degrees Celsius, and the time of the high-temperature calcination is 2 to 4 hours.

[0040] According to claim 1, use of the cerium-zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst in catalytic reduction of organic pollutants in water, wherein the organic pollutant is p-nitrophenol.

[0041] The catalyst uses nano-spherical ferroferric oxide as its core, and its magnetic properties make it easy to repeatedly recycle the catalyst during use. Ferroferric oxide has good electron transport properties, so it has a certain catalytic effect. Cerium-zirconium solid solution has excellent redox properties, oxygen storage and release properties, and electron transport properties, so it can be used as an electron transport intermediate layer to transfer electrons to the outer layer of the active component, thereby enhancing the reduction effect of the active sites on p-nitrophenol. Titanium oxide in cobalt titanate has a high specific surface area, which can promote the adsorption and activation of p-nitrophenol at the micro-interface of the active component, while cobalt oxide has excellent catalytic reduction properties. In the above-mentioned ferroferric oxide, cerium-zirconium solid solution and titanate, the catalyst can be used as a catalyst to promote the adsorption and activation of p-nitrophenol at the micro-interface of the active component. The sandwich structure of cobalt can effectively ensure the excellent catalytic effect and good recycling performance of the catalyst on p-nitrophenol; in addition, D-(-)-quinic acid, due to its weak acidity, can promote the uniform growth of cerium-zirconium solid solution on the outer surface of ferrosoferric oxide and the uniform growth of cobalt titanate on the outer surface of cerium-zirconium solid solution, so that the final catalytic material still maintains a nano-spherical shape, promotes the increase of the specific surface area of ​​the catalyst, and thus enhances its catalytic effect; finally, the hydrolysis reaction of titanium salts such as tetrabutyl titanate is too intense, and it is easy for cobalt titanate to not grow uniformly on the outer surface of cerium-zirconium solid solution. Therefore, the titanium salt is slowly contacted and hydrolyzed with air during water bath stirring, thereby achieving uniform growth of the catalytic material.

[0042] Embodiment 2:

[0043] Preparation of ferroferric oxide coated with cerium-zirconium solid solution:

[0044] Weigh 20 g of nano-iron tetroxide powder with a microscopic particle size of 300 nm, 13.873 g of cerium chloride, 6.365 g of zirconium nitrate, 0.4 g of D-(-)-quinic acid and 400 g of deionized water, mix them evenly, then place them in a hydrothermal reactor for hydrothermal reaction at 140° C. for 8 h, filter them after the reaction is completed, place them in an oven for drying at 80° C. for 12 h, and then place them in a muffle furnace for high-temperature calcination at 500° C. for 4 h to obtain cerium-zirconium solid solution-coated iron tetroxide powder;

[0045] Preparation of cobalt titanate solid solution:

[0046] Weigh 43.970g of acetic acid, 43.970g of deionized water and 527.640g of anhydrous ethanol into an open beaker and stir evenly, then add 8.794g of tetrabutyl titanate, 4.727g of cobalt nitrate and the cerium zirconium solid solution prepared in step S1 to wrap the ferroferric oxide powder and stir evenly to form a mixed slurry, then place the mixed slurry in a water bath and stir continuously, the water bath temperature is 60°C, the stirring rate is 50r / min, after stirring for 12h, the titanium salt in the mixed slurry is completely hydrolyzed, 0.264g of D-(-)-quinic acid is added and placed in a hydrothermal reactor for hydrothermal reaction at 140°C for 6h, after the reaction is completed, filter and place in an oven for drying at 100°C for 6h, then place in a muffle furnace for high temperature roasting at 600°C for 2h to obtain a cobalt titanate solid solution catalyst, and the catalyst FE-SEM image is as shown Figure 1 As shown, based on the mass of the ferroferric oxide core, the mass percentage of the electron transport intermediate layer is 60%, and the mass percentage of the active component outer layer is 20%; wherein the molar ratio of cerium oxide to zirconium oxide in the cerium-zirconium solid solution is 1:0.33;

[0047] Performance evaluation:

[0048] A 4 mL catalyst sample was loaded into a catalyst performance evaluation reaction device, and a reaction solution was introduced for activity evaluation; the concentrations of each solution were: 20 mL p-nitrophenol 100 mg / L, 20 mL sodium borohydride 3.78 g / L; at room temperature and pressure, the catalyst had an efficiency of 100% in removing p-nitrophenol, with an average removal rate of 6 mL / min, and the efficiency of the catalyst could still be maintained at 100% after being used ten times.

[0049] Embodiment three:

[0050] Preparation of ferroferric oxide coated with cerium-zirconium solid solution:

[0051] Weigh 20 g of nano-iron tetroxide powder with a microscopic particle size of 400 nm, 12.823 g of cerium nitrate hexahydrate, 28.550 g of zirconium oxychloride octahydrate, 1.0 g of D-(-)-quinic acid and 800 g of deionized water, mix them evenly, then place them in a hydrothermal reactor for hydrothermal reaction at 160° C. for 4 h, filter them after the reaction is completed, place them in an oven for drying at 100° C. for 6 h, and then place them in a muffle furnace for high-temperature calcination at 600° C. for 2 h to obtain cerium-zirconium solid solution-coated iron tetroxide powder;

[0052] Preparation of cobalt titanate solid solution:

[0053] Weigh 117.890g of acetic acid, 23.578g of deionized water and 471.560g of anhydrous ethanol into an open beaker and stir evenly, then add 11.789g of tetraethyl titanate, 6.710g of cobalt chloride and the cerium zirconium solid solution prepared in step S1 and wrap the ferroferric oxide powder and stir evenly to form a mixed slurry, then place the mixed slurry in a water bath and stir continuously, the water bath temperature is 80°C, the stirring rate is 100r / min, and the titanium salt in the mixed slurry is completely hydrolyzed after stirring for 24h Then, 0.118 g of D-(-)-quinic acid was added and the mixture was placed in a hydrothermal reactor for hydrothermal reaction at 120° C. for 12 h. After the reaction, the mixture was filtered and placed in an oven for drying at 80° C. for 12 h. The mixture was then placed in a muffle furnace for high-temperature roasting at 500° C. for 4 h to obtain a cobalt titanate solid solution catalyst. The mass percentage of the electron transport intermediate layer was 80% and the mass percentage of the active component outer layer was 40% based on the mass of the ferroferric oxide core. The molar ratio of cerium oxide to zirconium oxide in the cerium-zirconium solid solution was 1:3.

[0054] Performance evaluation:

[0055] A 4 mL catalyst sample was loaded into a catalyst performance evaluation reaction device, and a reaction solution was introduced for activity evaluation; the concentrations of each solution were: 20 mL p-nitrophenol 100 mg / L, 20 mL sodium borohydride 3.78 g / L; at room temperature and pressure, the catalyst had an efficiency of 100% in removing p-nitrophenol, with an average removal rate of 8 mL / min, and the efficiency of the catalyst could still be maintained at 100% after being used ten times.

[0056] Comparative Example 1:

[0057] Catalyst preparation:

[0058] Except that D-(-)-quinic acid was not used as a morphology control agent during catalyst preparation, other conditions were the same as those in Example 2;

[0059] Performance evaluation:

[0060] A 4 mL catalyst sample was loaded into a catalyst performance evaluation reaction device, and a reaction solution was introduced to evaluate the activity; the concentrations of each solution were: 20 mL p-nitrophenol 100 mg / L, 20 mL sodium borohydride 3.78 g / L; the catalyst had a p-nitrophenol removal efficiency of 61.3% at room temperature and pressure, and an average removal rate of 6 mL / min;

[0061] Contrast effect:

[0062] Compared with Example 2, when D-(-)-quinic acid is not used as a morphology control agent during the preparation of the catalyst, the catalyst will form a nano-coral-like structure. Figure 2,Although the coral-like particles also have a porous structure, the nanoparticles will aggregate, resulting in a reduced contact area between the catalyst and the reaction molecules, and a significant decrease in the removal efficiency of organic matter.

[0063] Comparative Example 2:

[0064] Catalyst preparation:

[0065] Except that the cerium-zirconium solid solution is not used as the electron transport intermediate layer when preparing the soil catalyst, other conditions are the same as those in Example 2;

[0066] Performance evaluation:

[0067] A 4 mL catalyst sample was loaded into a catalyst performance evaluation reaction device, and a reaction solution was introduced to evaluate the activity; the concentration of each solution was: 20 mL p-nitrophenol 100 mg / L, 20 mL sodium borohydride (3.78 g / L); the catalyst had a p-nitrophenol removal efficiency of 42.1% at room temperature and pressure, and an average removal rate of 8 mL / min;

[0068] Contrast effect:

[0069] Compared with Example 3, the cerium-zirconium solid solution is not used as the electron transport intermediate layer during the catalyst preparation, the redox performance of the promoter is lacking, the oxygen vacancy concentration is also reduced, and the catalytic performance is significantly reduced.

[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Cerium-zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst, characterized in that: include: Nano-spherical ferroferric oxide, cerium-zirconium solid solution, cobalt titanate and D-(-)-quinic acid, wherein the nano-spherical ferroferric oxide is the inner core, the cerium-zirconium solid solution is the electron transport middle layer, the cobalt titanate is the outer layer of the active component, and the D-(-)-quinic acid is the morphology control agent. Based on the mass of the ferroferric oxide inner core, the mass percentage of the electron transport middle layer is 60% to 80%, and the mass percentage of the active component outer layer is 20% to 40%; wherein the molar ratio of cerium oxide to zirconium oxide in the cerium-zirconium solid solution is 1:(0.33-3).

2. A method for preparing a cerium-zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst, characterized in that: The following steps are involved: S1. Preparation of ferroferric oxide coated with cerium zirconium solid solution, weighing nano ferroferric oxide powder, cerium salt, zirconium salt, D-(-)-quinic acid and deionized water, and then placing it in a hydrothermal reactor for hydrothermal reaction. After the reaction is completed, it is filtered and dried, and then calcined at high temperature to obtain cerium zirconium solid solution coated ferroferric oxide powder; S2. Preparation of cobalt titanate solid solution: weigh acetic acid, deionized water and anhydrous ethanol, put them in an open beaker and stir evenly, then add titanium salt, cobalt salt and the cerium-zirconium solid solution prepared in step S1 to wrap the ferroferric oxide powder and stir evenly to form a mixed slurry, then put the mixed slurry in a water bath and stir continuously, after the titanium salt in the mixed slurry is completely hydrolyzed, add D-(-)-quinic acid and put it in a hydrothermal reactor for hydrothermal reaction, filter and dry after the reaction, and then calcine at high temperature to obtain the cobalt titanate solid solution catalyst.

3. The method for preparing the cerium-zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst according to claim 2, characterized in that: The microscopic particle size of the nano-iron tetroxide powder in step S1 is 300-400 mm, the cerium salt is cerium chloride or cerium nitrate hexahydrate, and the zirconium salt is zirconium nitrate or zirconium oxychloride octahydrate.

4. The method for preparing the cerium-zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst according to claim 2, characterized in that: In step S1, the mass ratio of nano-iron tetroxide powder, D-(-)-quinic acid and deionized water is 1: (0.02-0.05): (20-40).

5. The method for preparing the cerium-zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst according to claim 1, characterized in that: In the step S1, the temperature of the hydrothermal reaction is 140 to 160 degrees Celsius, the time of the hydrothermal reaction is 4 to 8 hours, the temperature of the drying is 80 to 100 degrees Celsius, the time of the drying is 6 to 12 hours, the temperature of the high-temperature calcination is 500 to 600 degrees Celsius, and the time of the high-temperature calcination is 2 to 4 hours.

6. The method for preparing the cerium-zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst according to claim 2, characterized in that: The titanium salt in step S2 is tetrabutyl titanate or tetraethyl titanate, and the cobalt salt is cobalt nitrate or cobalt chloride.

7. The method for preparing the cerium-zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst according to claim 2, characterized in that: In the step S2, the mass ratio of titanium salt, acetic acid, deionized water, anhydrous ethanol and D-(-)-quinic acid is 1:(5-10):(2-5):(40-60):(0.01-0.03).

8. The method for preparing the cerium-zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst according to claim 2, characterized in that: In the step S2, the temperature of the water bath is 60 to 80 degrees Celsius, the stirring rate is 50-100 r / min, and the time for hydrolysis of titanic acid is 12 to 24 hours.

9. The method for preparing the cerium-zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst according to claim 2, characterized in that: In the step S2, the temperature of the hydrothermal reaction is 120 to 140 degrees Celsius, the time of the hydrothermal reaction is 6 to 12 hours, the temperature of the drying is 80 to 100 degrees Celsius, the time of the drying is 6 to 12 hours, the temperature of the high-temperature calcination is 500 to 600 degrees Celsius, and the time of the high-temperature calcination is 2 to 4 hours.

10. Use of the cerium-zirconium supported cobalt titanate solid solution nanosphere water treatment catalyst according to claim 1 in catalytic reduction of organic pollutants in water, wherein the organic pollutant is p-nitrophenol.

Citation Information

Cited By

  • Composite polymer microsphere for extracting and purifying chloro-polyfluoroalkyl ether sulfonic acid in urine as well as preparation method and application of composite polymer microsphere

    CN120385779A